Abortus Inkomplit pada Masyarakat Kabupaten Maros - Rahman, Nur Syafitri; Putra, Bayu Pratama; Murnita, Ika Azdah (Fakultas Kedokteran Universitas Bosowa, 2023)
Incomplete abortion is the partial production of the result of conception in pregnancy before 20 weeks, with there remaining left in the uterus. The purpose of this study was to determine the factors related to the incidence of incomplete abortion in pregnant women who were hospitalized in the Obstetrics and Gynecology Department of RSUD dr. La Palaloi Maros 2021. The study population was pregnant women who had an abortion, with a total sample of 79 samples that were determined using the total sampling technique. The research design is cross-sectional and quantitative analytic. Data analysis included univariate and bivariate data using the chi-square test. The result showed that the age group of mothers at risk (41,8%) and age of mothers not at risk (58,2%) with a p-value 0,041; the history of risk abortion (30,4%) and the history of non-risk abortion (69,6%) with a p-value 0,782; at-risk interpregnancy interval (35,4%) and not at-risk interpregnancy interval (64,6%) with a p-value 0,007; at risk hemoglobin levels (55,7%) and non-risk hemoglobin levels (44,3%) with a p-value 0,117; risk jobs (19,0%) and non-risk jobs (81,0%) with a p-value 0,338. The conclusion of the study at RSUD dr. La Palaloi Maros 2021 that there is a relationship between the age of the mother and the distance between pregnancies and the incidence of incomplete abortion